A Standard Structure for Bile Acids and Derivatives - Francisco Meijide; Santiago de Frutos; Victor H. Soto; Aida Jover; Julio A. Seijas; María Pilar Vázquez-Tato; Francisco Fraga; José Vázquez Tato (Crystals, 2018)
The crystal structures of two ester compounds (a monomer in its methyl ester form, with an amino isophthalic group, and a dimer in which the two steroid units are linked by a urea bridge recrystallized from ethyl acetate/methanol) derived from cholic acid are described. Average bond lengths and bond angles from the crystal structures of 26 monomers and four dimers (some of them in several solvents) of bile acids and esters (and derivatives) are used for proposing a standard steroid nucleus. The hydrogen bond network and conformation of the lateral chain are also discussed. This standard structure was used to compare with the structures of both progesterone and cholesterol.